Expanding the Field of Political Communication: Making the Case for a Fresh Perspective Through “Propaganda Studies” - Robinson, Piers (Frontiers in Communication, 2019)
Understanding how power is exercised through communication is central to understanding the socio-political world around us. To date, however, political communication research has been limited by an over-emphasis on 'problem solving' research which, by and large, reflects the interests and concerns of more powerful political actors. Even the marginalised critical political communication literature is limited by is focus on only media. To resolve these limitations, this paper argues that critical propaganda studies can help to widen and deepen the reach of existing political communication research. It can do so by alerting us to the wide range of actors involved in propaganda production and dissemination, including governments, academics, NGOs, think tanks and popular culture, as well as the manipulative and non-consensual modes of persuasive communication, including deception, incentivization and coercion. As such, a research agenda based on critical propaganda studies can provide a fuller and more accurate understanding of the role of communication in the exercise of power, serving better the objectives of speaking truth to power, holding power to account and facilitating better, more democratic, forms of organised persuasive communication. A research agenda based upon critical propaganda studies is